2017
DOI: 10.3991/ijoe.v13i08.7371
|View full text |Cite
|
Sign up to set email alerts
|

An Educational Physics Laboratory in Mobile Versus Room Scale Virtual Reality – A Comparative Study

Abstract: Abstract-The emergence of new digital tools supporting immersive and engaging learning through Virtual Reality is opening up new paths for both distance, but also classroom learning. In this article we discuss the virtual physics laboratory "Maroon" and discuss experiences with Maroon in a cost-effective mobile setup with a mobile VR experience through Samsung GEAR and compare it with a more interactive VR experience in room-scale VR with HTC Vive. We describe a comparative evaluation of these two setups in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Five educational approaches, one methodology, five learning theories and one theoretical framework were found in the included literature from the seventeen studies that were obtained from the Scopus database (as shown in the Table 2 and Figure 2). [29] Experiential Learning (Methodology) Akman and Çakır, 2019 [30] Flow Theory (Theory) Chang et al, 2018 [31], Remolar et al, 2021 [32] John Dewey's theory of learning by doing (Theory) Sedlák et al, 2022 [20] Learning through problem solving (LPS) (Educational approach) Sedlák et al, 2022 [20] Scientific discovery learning (SDL) (Educational approach) Southgate et al, 2018 [33] Social Constructivism (Theoretical framework)…”
Section: Theories Approaches and Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Five educational approaches, one methodology, five learning theories and one theoretical framework were found in the included literature from the seventeen studies that were obtained from the Scopus database (as shown in the Table 2 and Figure 2). [29] Experiential Learning (Methodology) Akman and Çakır, 2019 [30] Flow Theory (Theory) Chang et al, 2018 [31], Remolar et al, 2021 [32] John Dewey's theory of learning by doing (Theory) Sedlák et al, 2022 [20] Learning through problem solving (LPS) (Educational approach) Sedlák et al, 2022 [20] Scientific discovery learning (SDL) (Educational approach) Southgate et al, 2018 [33] Social Constructivism (Theoretical framework)…”
Section: Theories Approaches and Methodologiesmentioning
confidence: 99%
“…Recent research has proven that VR is beneficial in facilitating experiential learning in a range of educational environments [29]. Experiential learning, for example, has been demonstrated to improve perceived educational outcomes, attract students' interest and enhance enjoyment [28].…”
Section: Experiential Learning (Exl)mentioning
confidence: 99%
“…Within learning science, physics has been researched very often (Clark et al., 2011; Masson, Bub, & Lalonde, 2011; Squire, Barnett, Grant, & Higginbotham. 2004; Pirker, Lesjak, & Gütl, 2018; Ullman, Spelke, Battaglia, & Tenenbaum, 2017). The eminently abstract nature of the conceptual content of physics poses a major challenge to the learner, which is why Anderson and Barnett (2013) claim that videogames and simulators provide an excellent scenario for involving students in studying complex scientific concepts.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual reality creates the illusion that a person is in a different place. It is defined as a highly interactive multimedia environment based on computers in which the user becomes a participant in a computer-generated world [13][14][15]. We consider the following definition [16] to be the most appropriate: Virtual reality as a multidisciplinary research area aimed at interactive human-computer-mediated simulations of artificial environments.…”
Section: Virtual Reality and Gamesmentioning
confidence: 99%